Factors relating to stroke prevention behavior in hypertension patients based on Health Promotion Model (HPM) theory in the Gubeng district area of Surabaya - Purnamasari, Ira; Firman, Firman; Nasrullah, Dede; Sumarliyah, Eni (Universitas Muhammadiyah Surabaya, 2025)
Stroke is the number one cause of disability in Indonesia. Stroke is a condition of loss of brain function caused by stopping the blood supply to the brain. The main risk factor for stroke is hypertension. Hypertension sufferers who have poor preventive behavior have the potential to experience a stroke. This study aimed to identify the dominant factors related to stroke prevention behavior based on the Health Promotion Model (HPM) theory in the Gubeng District area of ​​Surabaya. This research used cross-sectional research with a sample of 108 respondents using purposive sampling. Data were collected using a questionnaire and analyzed using the logistic regression test α < 0.05. Independent factors related to stroke prevention behavior are perceived self-efficacy (0.000), activity-related affect (0.002), personal influences (0.000), and situational influences (0.023). Meanwhile, factors that have no relationship are prior related behavior (0.360), personal factor (motivation) (0.319), perceived benefits to action (0.200), perceived barriers to action (0.243), education level (0.708), socio-economic status (0.105). In conclusion, this research can be used as material for developing health workers' knowledge in intervening related to stroke prevention behavior in hypertension sufferers.